Tremor in cats: the effect of administration of drugs into the cerebral ventricles - Domer, F. R. (1960)
In cats, tremor produced by intraperitoneal pentobarbitone sodium or by intramuscular chlorpromazine was abolished by injection into the cerebral ventricles of a few gamma of adrenaline or noradrenaline, but not of other sympathomimetic amines or of anti-Parkinsonian drugs. Chloralose, urethane, calcium chloride, and magnesium chloride produced anti-tremor activity when administered in this way. When adrenaline or noradrenaline was perfused from a lateral ventricle to the aqueduct during pentobarbitone sodium tremor, tremor was inhibited when less than 1 μg. had been perfused. Adrenaline was at least four times as active as noradrenaline. Isoprenaline inhibited tremor when perfused in higher concentrations, but perfusion of ephedrine, amphetamine or of the anti-Parkinsonian drugs in high concentrations was ineffective. Perfusion of 2 μg. of chloralose or of 20 μg. of calcium chloride was sufficient to inhibit tremor. Intraventricular injections of 250 to 500 μg. of 5-hydroxytryptamine initiated tremor. Possible physiological implications of these findings are discussed.